Evaluation of the Perception of the Effectiveness of Financial Information Systems with the DeLone and McLean Methods - Riski Arifiyanti; Muhammad Shobaruddin; Alfi Haris Wanto (Wacana Journal of Social and Humanity Studies, 2020)
This study aims to measure the effectiveness of Financial Information Systems at the State University of Malang in 2019. Respondents in this study are UM stakeholders, namely system operators, system technicians and information users. Data collection using a questionnaire. The analysis used is Partial Least Square Analysis which is operated through the Smart PLS program. The results showed that there was no influence between the Quality of the System on Use in the information user and technician groups, conversely in the system user group there was an influence. There is an influence between Service Quality on Use in the information and technical user groups, conversely in the system user group there is none. There is no effect of system quality, information quality, and service quality on user satisfaction. There is an influence between users on user satisfaction on the group of users of information and systems, conversely there is no influence on the group of technicians. There is an influence between users on net benefits. There is an influence between user satisfaction on net benefits in the information user group and the system, conversely in the engineering group there is no influence.